Remoção de corante de efluentes da indústria têxtil utilizando processos com membranas e adsorção em bagaço de laranja - Ferrari, Leila Denise Fiorentin (2009)
The textile effluent when released into bodies' receptors may cause serious environmental problems due to its high load of contaminants. The treatment of wastewater generated by industrial processes can be achieved by various techniques, among them, the processes of membrane separation and adsorption show great capacity of dye retention. This research aimed to study the removal of reactive blue 5G dye of a synthetic textile effluent using the processes of membrane separation and adsorption in the orange pulp. The assays of textile dye removal in the effluent had been carried through using polymers membranes synthesized with polysulfone and applied in ultrafiltration module. The influence parameters to the process development was evaluated, as transmembrane pressure, membrane composition, average diameter of pores, pH of solution, membrane degradation and the fouling index. The results had shown that the membranes of composition 16.4% of polisulfone and 3% of KCL had removed about 70% of the present dye in the solution fed with concentration of 70 ppm, presenting a fouling index of 9.30%. The operation pressure was of 1.0 bar, the apparent membrane average pores radius was of 0.0134 μm and the solution pH presented mainly influence in the percentage of removal of dye, being the membrane susceptible to pH changes. The orange pulp used in the adsorption assays was submitted to convective drying in temperatures that had varied in the range of 33 to 92±1 ºC, remaining the air speed constant in 1.3 m/s. The equilibrium isotherms were determined by static and dynamic methods at temperatures of 25, 35 and 50 °C. To the data of drying and the equilibrium isotherms empirical and semi-empirical models presented in literature had applied. The results had shown that the increase of the temperature of air exerts direct influence in the constant rate period of drying and that the Page model was that better represented the data of drying in all the studied temperatures. In relation to the equilibrium isotherms it was verified that the temperature increase cause a rise in the moisture equilibrium of the orange pulp, due to the presence of orange peel. For the equilibrium isotherms, determined by static method, the models of Luikov (1992) and Halsey (1976) presented the best values of the statistical tests, while for the isotherms determined by the dynamic method, the model of Sabbah (2001) presented better adjustment. The adsorptions assays had been carried through in batch and continuous process. The results in batch had shown that, solution pH equal to 2, particles size of 0.17 mm and drying temperature of 42°C favors the adsorption of the dye in the pulp with superficial area of 2.76±0.02 m²/g. The solution temperature did not exert significant influence on the adsorption of the dye in orange pulp. The equilibrium data in temperature of 25 °C can be represented by the Langmuir isotherm with qmax=44.807 mg dying/g adsorbent. The adsorbent in study presented good results when submitted to desorption, and in pH 10 a 97% dye reduction in the pulp was obtained. In the process of continuous adsorption, the ruptures curves had shown that satisfactory removal of dye feed with concentration of 70 ppm is not obtained. The best conditions had been obtained to dye feed with concentration of 20 ppm and bed height of 15 cm, where the flow rate of 1.0 mL/min was the one that obtain a minor ZTM, with a useful capacity at 43.385 mg dying/g adsorbent. The combined process of membrane and adsorption presented satisfactory performance in dye removal, therefore with a feeding in the membrane of a dye solution with 70 ppm, gets a permeated with a concentration of 20 ppm, which submitted to continuous adsorption in orange pulp supplied an effluent free of dye.